Lanthanide-doped inorganic halide perovskites (CsPbX3): Novel properties and emerging applications - Kachhap S.; Singh S.; Singh A.K.; Singh S.K. (My University, 2025)
Inorganic halide perovskites (IHPs) have provoked intense research efforts because of their superior stability, excellent optoelectronic properties, cost-effectiveness, and striking optoelectronic applications. Recently, the doping of lanthanide ions in IHPs has opened new avenues, particularly for emerging applications like NIR and white light-emitting diodes, NIR emitters, NIR cameras, optical temperature sensing, optical data encoding, etc. Besides, lanthanide doping has also significantly improved the stability (thermal, photo, and phase), structure and optical properties of IHPs, which has resulted in improved device performance. However, a comprehensive review of this development for IHPs is rare. This review article is an attempt to fill this gap and is designed to provide important fundamental aspects as well as recent developments in the field. It comprises all the basics, synthesis strategies, crystal structure (including phase transition and phase stability), and optical properties (absorption, emission, lifetime, quantum yield, exciton binding energy, and anisotropy) for pristine IHPs with special reference to CsPbX3 (X = Cl, Br and I). The effects of lanthanide doping on the above-listed properties for IHPs are explored, and the doping of non-lanthanide metal ions such as alkali metals, alkaline earth metals, transition metals, and post-transition metals in all-IHPs are also covered for comparison. Furthermore, the review specifically outlines a few novel applications, which are due to the inherent merits of lanthanide doping in CsPbX3. Potential challenges and future perspectives are also discussed. © 2022 Royal Society of Chemistry. All rights reserved.